2023
DOI: 10.16970/entoted.1216414
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) popülasyonlarının yerel Bacillus thuringiensis suşlarına duyarlılığı

Abstract: Tomato leafminer, Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) is one of the most important tomato pests worldwide and causes 100% product loss if not controlled. Chemical insecticides, which have been overused for many years, have induced resistance in the pests and made it difficult to control their populations in the field. The use of biological agents that express insecticidal proteins, such as Bacillus thuringiensis, is an alternative to conventional insecticides to suppress pest populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Usta (2022), Bt from Cydalima perspectalis collected from Artvin province and reported that this bacterium showed an 85% mortality rate on the pest. Eski (2023) tested 13 local Bt strains isolated from soil samples for the control of Tuta absoluta and declared that Bt-B3 isolate is a promising biological warfare agent for integrated pest control of T. absoluta in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Usta (2022), Bt from Cydalima perspectalis collected from Artvin province and reported that this bacterium showed an 85% mortality rate on the pest. Eski (2023) tested 13 local Bt strains isolated from soil samples for the control of Tuta absoluta and declared that Bt-B3 isolate is a promising biological warfare agent for integrated pest control of T. absoluta in Turkey.…”
Section: Introductionmentioning
confidence: 99%